Exchange coupling torque in ferrimagnetic Co/Gd bilayer maximized near angular momentum compensation temperature - Robin Bläsing (Nature Portfolio, 2018)
High speed current induced domain wall motion is key to various spintronic applications, such as memory-storage. Here the authors show that the motion of chiral domain walls in Co/Gd bilayer structures is controlled by an exchange coupling torque that is maximized at the temperature where the Co and Gd angular momenta exactly balance each other